Antecedents and consequences of panic buying: The case of COVID‐19. (27th January 2021) - Prentice, Catherine; Quach, Sara; Thaichon, Park
Abstract: Panic buying emerged as a significant phenomenon during the COVID‐19 pandemic. This study draws on the scarcity principle, crowd psychology and contagion theory to investigate the antecedents and consequences of panic buying. The antecedents included in this study are government measures, media and peer influence and the fear of missing out. The consequences are founded on a sense of security and guilt. Retailer intervention is included as a moderator to the proposed main effects. Data were collected from 341 consumers who engaged in panic buying and were residents of the United States and Australia during the COVID‐19 pandemic. Structural equation modelling was employed to test the proposed model. The results show that the proposed antecedents (except fear of missing out) were significantly related to panic buying, which in turn had a significant influence on panic buyers' psychological outcomes. The moderating effects of retailer intervention varied across different product categories. Discussion and implications of these findings are provided for policy makers, customers and practitioners.